Technical support and delegation to practice staff: status quo and (possible) future perspectives for primary health care in Germany - Urban, Elisabeth; Ose, Dominik; Joos, Stefanie; Szecsenyi, Joachim; Miksch, Antje (BMC medical informatics and decision making, 2012)
Primary health care in industrialized countries faces major challenges due to demographic changes, an increasing prevalence of chronic diseases and a shortage of primary care physicians. One approach to counteract these developments might be to reduce primary care physicians’ workload supported by the use of health information technology (HIT) and non-physician practice staff. In 2009, the U.S. Commonwealth Fund (CWF) conducted an international survey of primary care physicians which the present secondary descriptive analysis is based on. The aim of this analysis was twofold: First, to explore to what extend German primary care physicians already get support by HIT and non-physician practice staff, and second, to show possible future perspectives.
Gesehen am 11.10.2018